Versatile on-chip polarization-sensitive detection system for optical communication and artificial vision - Zhilin Liu; Mingxiu Liu; Liujian Qi; Nan Zhang; Bin Wang; Xiaojuan Sun; Rongjun Zhang; Dabing Li; Shaojuan Li (Light: Science & Applications)
Abstract Polarization is an important attribute of light and can be artificially modulated as a versatile information carrier. Conventional polarization-sensitive photodetection relies on a combination of polarizing optical elements and standard photodetectors, which requires a substantial amount of space and manufacturing expenses. Although on-chip polarized photodetectors have been realized in recent years based on two-dimensional (2D) materials with low-symmetry crystal structures, they are limited by the intrinsic anisotropic property and thus the optional range of materials, the operation wavelength, and more importantly, the low anisotropic ratio, hindering their practical applications. In this work, we construct a versatile platform that transcends the constraints of material anisotropy, by integrating WSe2-based photodetector with MoS2-based field-effect transistor, delivering high-performance broadband polarization detection capability with orders of magnitude improvement in anisotropic ratio and on/off ratio. The polarization arises from hot electron injection caused by the plasmonic metal electrode and is amplified by the transistor to raise the anisotropic ratio from 2 to an impressive value over 60 in the infrared (IR) band, reaching the level of existing applications. Meanwhile, the system achieves a significant improvement in photosensitivity, with an on/off ratio of over 103 in the IR band. Based on the above performance optimization, we demonstrated its polarization-modulated IR optical communication ability and polarized artificial vision applications with a high image recognition accuracy of ~99%. The proposed platform provides a promising route for the development of the long-sought minimized, high-performance, multifunctional optoelectronic systems.